THEORETICAL ASPECTS ABOUT TASKS THAT DEVELOP THE SPATIAL VISUALIZATION SKILLS - Silva, Cristian Martins da (2023)
Spatial Visualization Skills (SVS) represent one of the pillars of geometric thinking, which is an important competence in cognitive and mathematical development. In this way, there are vast researches that investigate and analyze these tasks and the need to understand which specific skills each type of task develops emerges. In this context, the objective of this article is to analyze how tasks that demand SVS have been classified throughout the literature. Therefore, this qualitative bibliographic research describes and correlates Del Grande's Spatial Skills (1994), Maier's Five Elements of Spatial Thinking (1996) and Visualization Actions by Gonzato, Fernández and Díaz (2011) with Categorization of Visualization Actions by Mathias and Simas (2021) designed for the analysis of textbook tasks that require SVS. Based on the discussions, this research expands the specific skills addressed by these authors and discusses how the Visualization Actions defined in Mathias and Simas (2021) broadly contemplate SVS and can be used as a basis for future analysis of visualization tasks.